Assessing the Efficiency of Double-Strand Break Repair Mediated by Homologous Recombination and Non-homologous End-Joining Pathways in Saccharomyces cerevisiae - Sugith Badugu; Kshitiza Dhyani; Kalappa Muniyappa (Bio-Protocol, 2025)
The DNA double-strand breaks (DSBs) generated by exogenous and endogenous factors are repaired by two pathways: homologous recombination (HR) and non-homologous end-joining (NHEJ). These two pathways compete for DSB repair, and the choice of pathway depends on the context of the DNA lesion, the stage of the cell cycle, and the ploidy in the yeast Saccharomyces cerevisiae. However, the mechanistic details of the DSB repair pathway choice and its consequences for S. cerevisiae genome stability remain unclear. Here, we present PCR-based and cell-based assays as well as data analysis methods to quantitatively measure the efficiency of HR and NHEJ at DSBs in S. cerevisiae. An intermolecular recombination assay between plasmid and chromosomal DNA involving G-quadruplex DNA and a “suicide-deletion” assay have been utilized to evaluate the efficiency of HR and NHEJ, respectively. These streamlined protocols and optimized growth conditions can be used to identify the NHEJ- and HR-deficient S. cerevisiae mutant strains.